Increased TRPV1 and PAR2 mRNA expression levels are associated only with the esophageal reflux symptoms, but not with the extraesophageal reflux symptoms. Issue 32 (August 2016) - Kim, Jin Joo; Kim, Nayoung; Choi, Yoon Jin; Kim, Joo Sung; Jung, Hyun Chae
Abstract : Abstract: Transient receptor potential vanilloid-1 (TRPV1) receptor and proteinase-activated receptor 2 (PAR2) have been implicated in the mechanism of acid-induced inflammation in gastroesophageal reflux disease (GERD). We aimed to evaluate TRPV1 and PAR2 mRNA expression levels in the GERD patients and their relationship with endoscopic findings and reflux symptoms. Sixteen healthy controls, 45 patients with erosive reflux disease (ERD), and 14 nonerosive reflux disease (NERD) patients received endoscopy and completed questionnaires. Quantitative real-time polymerase chain reactions (qPCR) of TRPV1, glial cell line-derived neurotrophic factor ( GDNF ), nerve growth factor ( NGF ), PAR2, and interleukin (IL)-8 were performed in the distal esophagus specimen. The levels of TRPV1, GDNF, NGF, PAR2, and IL-8 mRNA expression were highest in the ERD group followed by NERD and control groups and the differences between control and ERD groups were statistically significant. Within the ERD group, patients with grade B in Los Angeles (LA) classification showed significantly higher levels of TRPV1, GDNF, and NGF mRNA expression than those with grade A. Presence of reflux symptoms was associated with significant higher levels of TRPV1, PAR2, and IL-8 . Notably not extraesophageal but esophageal reflux symptoms were significantly associated with them. Upregulation of TRPV1 and PAR2 pathways might play a role in the development of distal esophageal inflammation and reflux symptoms. And extraesophageal reflux symptoms might not be associated with these processes.